El Principe Caspian - Lewis, C. S. (Clive Staples), 1898-1963. (Santiago de Chile : Andres Bello, 1996)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.
Translation of: Prince Caspian.
Keywords: Narnia (Imaginary place) -- Fiction; Good and evil -- Fiction